Integrated application of bacterial carbonate precipitation and silicon nanoparticles enhances productivity, physiological attributes, and antioxidant defenses of wheat (Triticum aestivum L.) under semi-arid conditions - Desoky, El-Sayed M.; Rady, Mostafa M.; Nader, Maha M.; Mostafa, Nadeen G.; Elrys, Ahmed S.; Mathai, Archana; AbuQamar, Synan F.; El-Tarabily, Khaled A.; El-Saadony, Mohamed T. (Frontiers in Plant Science, 2022)
The use of calcium carbonate-precipitating bacteria (CCPB) has become a well-established ground-improvement technique. However, the effect of the interaction of CCPB with nanoparticles (NPs) on plant performance is still meager. In this study, we aimed at evaluating the role of CCPB and/or silicon NPs (Si-NPs) on the growth, physio-biochemical traits and antioxidative defense of wheat (Triticum aestivum L.) under semi-arid environmental conditions. Therefore, a 2-year pot experiment was carried out to determine the improvement of the sandy soil inoculated with CCPB and the foliar application of Si-NPs on wheat plants. We tested the following treatments: Spraying plants with 1.0- or 1.5-mM Si-NPs (control = 0 mM Si-NPs control), soil inoculated with Bacillus lichenforms (MA16), Bacillus megaterium (MA27), or Bacillus subtilis (MA34), and the interaction of individual Bacillus species with Si-NPs. Our results showed that soil inoculation with any of the three isolated CCPB and/or foliar application of Si-NPs at the rates of 1.0 or 1.5 mM significantly improved (p ≤ 0.05) the physiological and biochemical attributes as well as the enzymatic antioxidant activities of wheat plants. Thus, the combined treatments of CCPB+Si-NPs were more effective in enhancing physio-biochemical characteristics and enzymatic antioxidant activities than the individual treatment of CCPB or Si-NPs; thus, achieving the best performance in the treatment of MA34+1.5 mM Si-NPs. Our results demonstrated that the co-application of CCPB and Si-NPs, particularly MA34+1.5 mM Si-NPs, considerably activated the antioxidant defense system to mitigate the adverse effects of oxidative stress, thus, increasing tolerance and enhancing production of wheat plants in sandy soils under semi-arid environmental conditions.